2022
DOI: 10.1002/agt2.267
|View full text |Cite
|
Sign up to set email alerts
|

Construction of fluorescent hyperbranched polysiloxane‐based clusteroluminogens with enhanced quantum yield and efficient cellular lighting

Abstract: Owing to its designability and intrinsic fluorescence, non‐conjugated hyperbranched polysiloxane (HBPSi) has attracted widespread attention in biological filed, while it is still severely restricted by low fluorescence efficiency. So, in this paper, we introduced disulfide into HBPSi improving their luminescence properties and synthesized different molecular weight HBPSi (P1, P2, and P3). Surprisingly, P1 exhibited ultrahigh quantum yield up to 47.81%. Meanwhile, experiments applied with theoretical calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…These confinement/immobilization strategies mainly include aggregation/clustering (i.e., supramolecular type), 31 chemical cross-linking (i.e., chemical type), 32,33 mechanical compression (i.e., physical type), 16 and dendrimer/dendritic confinement (i.e., architectural type). 34,35 Such strategies to achieve "molecular confinement, immobilization, or rigidification" have been applied to create novel, active molecular states with through-space electronic communication/interactions that are presumed to be new molecular quantum states. 16 In addition, Feng et al reported that Si coordination with heteroatoms causes silicone-induced aggregation and endows silicone/siloxane-based polymers with NTIL properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These confinement/immobilization strategies mainly include aggregation/clustering (i.e., supramolecular type), 31 chemical cross-linking (i.e., chemical type), 32,33 mechanical compression (i.e., physical type), 16 and dendrimer/dendritic confinement (i.e., architectural type). 34,35 Such strategies to achieve "molecular confinement, immobilization, or rigidification" have been applied to create novel, active molecular states with through-space electronic communication/interactions that are presumed to be new molecular quantum states. 16 In addition, Feng et al reported that Si coordination with heteroatoms causes silicone-induced aggregation and endows silicone/siloxane-based polymers with NTIL properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The key point of these two mechanisms is the intra-and/or intermolecular through-space conjugation (TSC) through the overlap or sharing of electron clouds of NCCs, [13] which leads to the formation of extended n-n, n-π and π-π conjugation and hence lowered energy levels, promoting electron transitions and photoluminescence emissions. Adjusting the chemical structures like the type of NCCs, [14] rigidity or flexibility of polymer chains [15,16] and intra-and/or intermolecular interactions are effective in promoting TSC and hence PL of NTLs.…”
Section: Introductionmentioning
confidence: 99%
“…24 Moreover, the Si O Si bond in the HBPSi structure has a large bond angle, and the vacant orbital on each Si atom is favorable for accepting electrons and forming coordination bonds, which prompts HBPSi to emit bright fluorescence. 25 Therefore, it can be predicted that the electronabsorbing effect of Cl or Br atoms can greatly change the electron delocalization of the entire HBPSi molecular system after the introduction of Cl or Br atoms into its structure, and affecting the AIE performance of HBPSi. Halogen atoms acting as electron-absorbing groups can not only strengthen the electrostatic force between molecules, which is conducive to intermolecular aggregation, but also broaden the fluorescence emission peak of the polymer due to its electron-donating conjugate effect.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with F atoms, Cl atoms and Br atoms are rarely studied, which possess larger atomic radius and more balanced electron effects, such as electron‐attracting induction effect and electron‐donating conjugation effect 24 . Moreover, the SiOSi bond in the HBPSi structure has a large bond angle, and the vacant orbital on each Si atom is favorable for accepting electrons and forming coordination bonds, which prompts HBPSi to emit bright fluorescence 25 . Therefore, it can be predicted that the electron‐absorbing effect of Cl or Br atoms can greatly change the electron delocalization of the entire HBPSi molecular system after the introduction of Cl or Br atoms into its structure, and affecting the AIE performance of HBPSi.…”
Section: Introductionmentioning
confidence: 99%